Don't Be Such a Scientist: Talking Substance in an Age of Style - Olson, Randy (Island Press, 2020)
Well. That was my introduction to Hollywood, complete with the personalized profanity. Thirty-eight years old. Just resigned from my tenured professorship of marine biology. Invested every cent o move to Hollywood. Entered film school at the University of Southern California and signed up for an acting class with this crazy teacher, now blowing her lungs out at me in front of the class.